Electrodeposition and characterisation of Ni/gelatin microgels coatings. (2nd January 2020) - Gibb, A.; Vorobjovs, A.; Jagoda, Z.; Winiarski, J.; Stankiewicz, A.
ABSTRACT: This work focuses on implementing microgels for carrying self-healing substances in protective coatings. Ni/gelatin microgels coatings were manufactured using electroplating techniques. Microscopic analysis was carried out to establish the presence of microgels in the coating. This was followed by an investigation into the influence of the microgels on the mechanical properties and corrosion resistance of the coatings. The composite Ni/gelatin microgels coating exhibited better wear resistance and higher hardness than the plain nickel coating. Electrochemical impedance analysis showed the difference in the corrosion behaviour of the coatings in 3.5 wt. % NaCl solution. Over the time of the immersion, the corrosion resistance of the nickel coatings decreased from 28 to 14 kΩ cm 2, while the composite coatings increased from 5.8 to 10 kΩ cm 2 . At this stage of the research, only microgels without any active compounds have been used, thus no information related to the self-healing characteristics of coatings is currently available.